Herpes simplex virus type 1 in peptic ulcer disease: An inverse association with Helicobacter pylori - Tsamakidis, Klisthenis (World J Gastroenterol, 2005)
AIM: To assess the frequency of herpes simplex virus type I in upper gastrointestinal tract ulcers and normal mucosa with the modern and better assays and also with a larger number of well characterized patients and controls and its relationship to Helicobacter pylori(H pylori). METHODS: Biopsy specimens from 90 patients (34 with gastric ulcer of the prepyloric area and 56 with duodenal ulcer) were evaluated. Biopsies from 50 patients with endoscopically healthy mucosa were considered as the control group. The method used to identify herpes simplex virus-1 (HSV-1) was polymerase chain reaction. H pylori was detected by the CLO-test and by histological method. RESULTS: Herpes simplex virus-1 was detected in 28 of 90 patients with peptic ulcer (31%) [11 of 34 patients with gastric ulcer (32.4%) and 17 of 56 with duodenal ulcer (30.4%)] exclusively close to the ulcerous lesion. All control group samples were negative for HSV-1. The likelihood of H pylori negativity among peptic ulcer patients was significantly higher in HSV-1 positive cases than in HSV-1 negative cases (P = 0.009). Gastric ulcer patients with HSV-1 positivity were strongly associated with an increased possibility of Helicobacter pylori negativity compared to duodenal ulcer patients (P = 0.010). CONCLUSION: HSV-1 is frequent in upper gastro-intestinal tract ulcers but not in normal gastric and duodenal mucosa. There is an inverse association between HSV-1 and H pylori infection.